Task based language learning and teaching with technology - Cardoso, Gisele Luz (Ilha do Desterro, 2014)
The book is not accessible to a wider audience since it is required from the reader some background knowledge regarding tBlt and Call. instead, it is geared toward, mostly, second language (l2) researchers and is divided into two parts: (1) research on tasks in Call (Chapters 2 to 6) and (2) applying technology- Mediated tasks (Chapters 7 to 10). in the "Foreword" section, professor rod ellis draws the readers' attention to the fact that it is true there are many books on tBlt, but little has been published about tBlt in technology-mediated environments, with the exception of Chapelle, 2001. [...]this book is a good service to tBlt research and is very welcome. The study reveals that reflective practice through standards-based e-portfolios fosters development in all aspects of tBlt and task-based teaching competencies by means of mutual asynchronous feedback, but more guided reflection process is needed to achieve these goals. [...]digital technologies can be of aid in teachers' education scenarios and improve task-based teaching competencies. [...]its rich theoretical background highlights the relevance of task design, multimodality and literacy skills inside computer- mediated collaborative tasks forlanguage learners and teachers development. [...]Motteram and Thomas take the readers back to the future, reminding them that technologies are always changing and when it comes to choice of technology-based tasks, it depends, most of all, on the teachers' and instructors' needs and possibilities in their networked classrooms. in this sense this book is also an important contribution for language pedagogy.